Perception Study on the Facilities for Walking. (Case Study of Bandarlampung, Indonesia) - Nuzir F A; Murwadi H (Bandar Lampung University (UBL), 2017)
Urban transport is single-handedly responsible for emitting approximately around one fourth of global carbon dioxide in the atmosphere. Therefore by improving the development of non-motorized transport modes, the emission could be substantially decreased. The non-motorized transport modes are often referred as low carbon transport mode as they emit zero to low level of carbon. Cycling and walking are the most popular form of low carbon transport with the later often receives less attention in conventional urban development. On previous studies, authors identified key-elements of Pedestrian Profile, Pedestrian Activity, and Pedestrian Environment which are being introduced by authors as its abbreviation, PL.AC.E. Authors designed a comprehensive questionnaire based on the framework as the tool for data collection and then analyzed it using statistical procedures. This method aimed to identify the propensity of each key-attribute in order to understand the characteristic of each key-attribute. On this study authors focused on analyzing the key element of Pedestrian Environment and utilized the evaluation method with the case study of the city of Bandar Lampung in Indonesia. The questionnaire was distributed to 189 respondents directly and via online form. Based on the propensity of the responses, authors concluded that the case study area represented a rather low level of service of the environment for pedestrian specifically of its walking facility